Milk procurement, markets and consumption patterns in Sri Lanka: Application of a dairy conceptual research framework - Ibrahim, Mohamed N.M.; Staal, Steven J.; Daniel, S.L.A.; Ganguly, B.K.; Thorpe, W.R. (2003)
Not available